Dimethyl sulfoxide prevents DNA nicking mediated by ionizing radiation or iron/hydrogen peroxide-generated hydroxyl radical. - Repine, J E (1981)
Eighty percent of the single-strand DNA breaks induced by gamma-irradiation were prevented by the hydroxyl radical (.OH) scavenger dimethyl sulfoxide (Me2SO); CH4 was generated in the process as a product of the interaction of .OH and Me2SO. In contrast, Me2SO completely blocked DNA nicking by an iron/H2O2 system which produces .OH but smaller amounts of CH4 from Me2SO. Because Me2SO prevented DNA breaks from the more efficient iron/H2O2 system but only blocked 80% of irradiation-mediated nicking, the results suggest that .OH is responsible for 80% of the DNA single-strand breaks and the remaining 20% is due to interactions not involving .OH.